Facile synthesis of flower-like hierarchical NiCo2O4 microspheres as high-performance cathode materials for Li–O2 batteries. Issue 101 (17th October 2016) - Wang, Liangjun; Zhu, Ting; Lyu, Zhiyang; Zhang, Jian; Gong, Lili; Xiao, Shuning; Liu, Jia; Dong, Wenhao; Cui, Xinhang; Ho, Ghim Wei; Chen, Wei
Abstract : The Li–O2 battery with flower-like hierarchical NiCo2 O4 microspheres cathode exhibits a low discharge/charge voltage gap of 0.86 V, much lower than previously reported results for NiCo2 O4 . Abstract : Development of efficient and cost-effective catalyst is one of the key issues for practical lithium–oxygen (Li–O2 ) batteries. Herein, we report a facile synthesis of flower-like hierarchical NiCo2 O4 microspheres as an effective cathode catalyst for Li–O2 batteries. The synthesized NiCo2 O4 microsphere consists of loosely interconnected nanopetals, which could simultaneously offer sufficient active sites, facilitate mass transfer of Li + /O2 and provide enough space for Li2 O2 deposition. When employed as the cathode catalyst for Li–O2 batteries, a low discharge/charge voltage gap of 0.86 V can be obtained, much lower than previously reported results for NiCo2 O4 . Meanwhile, flower-like NiCo2 O4 shows improved discharge capacity (3163 mA h g −1 at 0.08 mA cm −2 ) and better cycle stability (60 cycles at 500 mA h g −1 capacity limit) compared with NiCo2 O4 nanoneedles and bare carbon cathode. The superior electrochemical performance of NiCo2 O4, together with the facile fabrication approach, makes NiCo2 O4 microspheres a promising candidate for Li–O2 batteries.